Influence of oxidizing environment to the scale formation of Ti-A1 based intermetallics - Astuty Amrin; Esah Hamzah; Mohd. Nasir Tamin; Stott, F. H.; Wood, G. C.; International Materials Technology (4th : 2004 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2004)
51